2002
DOI: 10.1046/j.1528-1157.2002.13802.x
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset Absence Epilepsy and Paroxysmal Dyskinesia

Abstract: Summary:Purpose: To report on the association of childhood absence epilepsy and paroxysmal dyskinesia (PD).Methods: We describe six patients aged 6 to 27 years (mean, 14 years) who were identified in five centers participating in a European study group. Patients had been followed up clinically from the first symptoms and had been studied with video-EEG recordings of absence seizures, videotaping of dyskinetic attacks, and brain magnetic resonance imaging (MRI).Results: Four patients were sporadic, and two were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…An interesting and increasingly recognized phenomenon is the coexistence of epilepsy and paroxysmal dyskinesia in the same individual (Guerrini 2001;Guerrini et al 2002). Despite the fact that the basic pathophysiology underlying that coexistence is unknown, both neurological disorders seems to be the clinical consequence from a gain-of-function mutation of BK channels leading to an increase in neuronal excitability (Du et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting and increasingly recognized phenomenon is the coexistence of epilepsy and paroxysmal dyskinesia in the same individual (Guerrini 2001;Guerrini et al 2002). Despite the fact that the basic pathophysiology underlying that coexistence is unknown, both neurological disorders seems to be the clinical consequence from a gain-of-function mutation of BK channels leading to an increase in neuronal excitability (Du et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy and PD have been reported to co-occur in various forms. Characteristically, epilepsy manifests as idiopathic syndrome, making a genetic cause plausible [Guerrini et al 2000]. A family with Rolando epilepsy with PED and writer's cramp with autosomal recessive inheritance was described by Guerrini and colleagues [1999] and has been linked to chromosome 16p, which is within the ICCA region.…”
Section: Geneticsmentioning
confidence: 99%
“…A number of studies have reported the coexistence of epilepsy and movement disorders in the same individuals or in different individuals within a family (Guerrini et al, 1999(Guerrini et al, , 2002Guerrini, 2001). In a recent report, a mutation was identified in a calcium-sensitive potassium channel in childhood-onset paroxysmal nonkinesigenic dyskinesia with absence epilepsy associated with rare tonicclonic seizures and generalized spike-wave complexes on electroencephalogram (Du et al, 2005).…”
Section: Epilepsy or Movement Disorder?mentioning
confidence: 99%